The tender years toward developmentally sensitive child welfare services for very young children - Berrick, Jill Duerr (New York ; Oxford : Oxford University Press, 1998)
The authors examine the impact of child abuse and neglect on preschool children and the handling of this population's needs by the child welfare system. An overview of child development theory and child abuse reporting patterns is presented, and the differences in the foster care experiences of the very young older children is analysed.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Preschool children -- Services for -- United States; Infants -- Services for -- United States; Foster children -- United States; Child welfare -- United States; Child development -- United States